Lexica Afroasiatica IX - Takács, Gábor (Lingua Posnaniensis, 2011)
Comparative-historical Afro-Asiatic linguistics has undergone significant development over the past half century, since the appearance of Essai comparatif sur le vocabulaire et la phonétique du chamitosémitique (1947) by Marcel Cohen. This revolutionary and fundamental synthesis concluded the second great period of the comparative research on Afro-Asiatic lexicon (the so-called “old school”, cf. EDE I 2–4). During the third period (second half of the 20th century), whose beginning was hallmarked by the names of J.H. Greenberg and I.M. Diakonoff, a huge quantity of new lexical material (both descriptive and comparative) has been published, including a few most recent attempts (either unfinishe or rather problematic) at compiling an Afro-Asiatic comparative dictionary (SISAJ a I–III , HCVA I–V, HSED , Ehret 1995). During my current work on the Etymological Dictionary of Egyptian (EDE ), I have collected a great number of new AA parallels, which – to the best of my knowledge – have not yet been proposed in the literature or were observed independently from me. Along the EDE project (and the underlying “Egyptian etymological word catalogue”), I have started collecting AA roots (not attested in Egyptian) for a separate Afro-Asiatic root catalogue in late 1999. The series Lexica Afroasiatica started in 2002 for communicating new Afro-Asiatic lexical correspondences observed recently during my work, which may later serve as basis of a new synthesis of the Afro-Asiatic comparative lexicon. The present part of this series is a collection of additional new Afro- Asiatic etymologies with the Proto-Afro-Asiatic initial bilabial nasal (*m-) observed after my research periods at Institut für Afrikanische Sprachwisenschaften of Frankfurt a/M (in 1999–2000 and 2002) guided by Prof. H. Jungraithmayr. The numeration of the etymological entries is continuous beginning from the first part of the series Lexica Afroasiatica. Each entry is headed by the proposed PAA root (as tentatively reconstructed by myself). Author names are placed after the quoted linguistic forms in square brackets [] mostly in an abbreviated form (a key can be found at the end of the paper). The lexical data in the individual lexicon entries have been arranged in the order of the current classification of the Afro-Asiatic daughter languages (originating from J. H. Greenberg 1955; 1963 and I. M. Diakonoff 1965) in 5 (or 6) equivalent branches: (1) Semitic, (2) Egyptian, (3) Berber, (4) Cushitic, (5) Omotic (cometimes conceived as West Cushitic), (6) Chadic. For a detailed list of all daughter languages cf. EDE I 9–34. The number of vertical strokes indicates the closeness of the language units from which data are quoted: ||| separate branches (the 6 largest units within the family), || groups (such as East vs. South Cushitic or West vs. East Chadic), while | divides data from diverse sub-groups (e.g., Angas-Sura vs. North Bauchi within West Chadic). Since we know little about the Proto-Afro-Asiatic vowel system, the proposed list of the reconstructed Proto-Afro-Asiatic forms is arranged according to consonantal roots (even the nominal roots). Sometimes, nevertheless, it was possible to establish the root vowel, which is given in the paper additionally in brackets. The lexical parallels suggested herein, are based on the preliminary results in reconstructing the consonant correspondences achieved by the Russian team of I. M. Diakonoff (available in a number of publications) as well as on my own observations refining the Russian results (most importantly Takács 2001). The most important results can be summarized as follows. The labial triad *b-*p-*f remained unchanged in Egyptian, South Cushitic, and Chadic, while the dental series *d-*t-*ṭ was kept as such by Semitic and South Cushitic (AA *ṭ continued as *ḍ in Berber, Cushitic and Chadic, and it was merged into t vs. d in Egyptian). The fine distinction of the diverse sibilant affricates and spirants (AA *c, *ʒ, *2, *s, *č, *ǯ, *2ˇ, *š, *ĉ, *2ˆ, *ŝ) was best preserved in Semitic, South Cushitic and West Chadic (while some of these phonemes suffered a merger in other branches and groups). The Russian scholars assumed a triad of postvelar (uvulear) stops with a voiceless spirant counterpart: *g, *q˙, *q, and *ḫ, the distinction of which was retained in Cushitic and Chadic, but was merged into *ḫ in Semitic and Egyptian. In a number of cases, however, it is still difficult to reconstruct exactly the root consonants on the basis of the available cognates (esp. when these are from the modern branches, e.g., Berber, Cushitic-Omotic, or Chadic). In such cases, the corresponding capitals are used (denoting only the place of articulation). This part contains new Afro-Asiatic roots with *n- followed by a labial.